Detection of Formalin Contamination in Fried Meatball Sold Around Darussalam Banda Aceh - Ismail Ismail; Sulasmi Sulasmi; Sahlan Harahap (Universitas Syiah Kuala, 2014)
The aims of this research was to identify formalin contained in fried meatball sold in Darussalam Banda Aceh. This research used fried meatballs collected from 10 different booths and examined in veterinary public health laboratory, Veterinary Medicine Faculty of Syiah Kuala University. The examination of formalin contained in fried meatballs was carried out using formalin test method. The result showed that all fried meatballs sold in Darussalam Banda Aceh examined did not contain formalin, proven by there was no colour change on the test and it was therefore save to consume.Key words: meatball, formalin